Uji Aktivitas Antibakteri Gel Minyak Atsiri Daun Kemangi (Oscimum basillicum L) Terhadap Staphylococcus aureus - Shoviantari, fenita; Turrohmah, Nur Annisa (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2021)
The essential oil of basil leaves (Oscimum basillicum L) has a mixture of chemical compositions, the most common of which are terpenes, aldehydes, alcohols, esters, phenols and ketones. Of these compounds that have antibacterial activity is linalool (51.2-74.73%) which is included in the terpenoid compound group. Objective: This study aims to determine whether there is an effect of the concentration of basil essential oil on the physical quality test of gel preparations and to determine whether there is a difference in the effect of the concentration of basil essential oil on antibacterial activity. The essential oil of basil leaves essential oil hand antiseptic gel was formulated with 4%, 6%, and 8% concentration of basil essential oil. Method: Antibacterial activity test was performed using the Disk Diffusion method. Results: The results of the research for the hand antiseptic gel of the essential oil of basil leaves (Oscimum basillicum L) met the parameters of the organoleptic test, homogeneity test, pH test, spreadability test and adhesion test. Basil leaf essential oil hand antiseptic gel with a concentration of 4% can inhibit bacterial growth with an average of 9mm, a concentration of 6% with an average of 10mm, and a concentration of 8% with an average of 12mm. By analyzing the data using One Way ANOVA, the Sig. 0,000 which means that there are differences in the three formulations. Conclusion: The three formulations are susceptible to strong inhibition.